Morphology, Formation, and Activity of Three Different Pockmark Systems in Peri-Alpine Lake Thun, Switzerland - Cojean, Adeline N. Y.; Kremer, Katrina; Bartosiewicz, Maciej; Fabbri, Stefano C.; Lehmann, Moritz F.; Wirth, Stefanie B. (Frontiers in Water, 2021)
Pockmarks are crater-like depressions formed by upward fluid flow (gas and/or liquid) through the unconsolidated sediment column on the floor of oceans and lakes. While pockmarks are well described in the marine realm, they have essentially been overlooked in lacustrine settings, likely due to a lack in economic interest to apply high-resolution hydroacoustic techniques in lakes. A swath-bathymetry survey on Lake Thun, Switzerland, revealed the existence of three pockmark systems. One pockmark (110 m in diameter) was discovered near a big karst system at Beatenberg at a water depth of 217 m. Its activity is probably associated with episodic groundwater seepage induced by earthquakes, floods and snowmelt. At another site, Daerligen, we detected at 60 m water depth the presence of multiple smaller pockmarks ( 1.5 to 10 m in diameter) that seem to be active, continuously liberating CH4 gas by bubble ebullition. The CH4 displayed a biogenic carbon isotopic signature, however, the exact origin of the gas remains unknown. The third site, Tannmoos ( 35 m water depth), comprises two large pockmarks (20–43 m in diameter) connected to a karst system in gypsum-carrying bedrock. One of these pockmarks is constituted of several unit pockmarks (e.g., sub-pockmarks; 0.3 to 0.8 m in diameter). While strong evidence is still lacking, we suggest that groundwater discharge occasionally occurs through these unit pockmarks during periods of intense precipitation. Hence, this study reveals the existence of three pockmark systems of variable morphology and mechanisms of formation within the same lake, reflecting different hydrological and biogeochemical regimes. Moreover, it underscores the potential importance of pockmarks in influencing hydrological and CH4 budgets in lakes. Clearly more work on quantifying seasonal fluxes of groundwater and CH4 release via lacustrine pockmarks is required, and it needs to be seen whether the observations made in Lake Thun are universal and apply also to many other lacustrine environments worldwide.